Preparation method and application of bio-based plastic starch slurry with medium-temperature water solubility

By enzymatic hydrolysis of starch, the introduction of amphiphilic groups and the treatment of ethanol base was prepared to prepare a bio-based plastic starch slurry with medium-warm water-soluble properties, which solved the clustering, wear resistance and The problem of ash residue has achieved efficient and environmentally friendly glass fiber yarn sizing effect.

CN119433981AActive Publication Date: 2025-02-14JIANGSU NEW REBA TECH CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411524778.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-14
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

When the existing medium and low temperature starch slurry is slurry on glass fiber yarn, it has poor clustering, low wear resistance and excessive ash residue, resulting in poor product quality.

Method used

Plasticizers are prepared by enzymatic hydrolysis of starch to improve the plasticity of the starch film; the introduction of amphiphilic groups reduces the surface tension of the slurry and enhances permeability; the ethanol base method is used to achieve medium-warm water solubility, and the slurry is improved through crosslinking and cationic modification performance of material.

Benefits of technology

It significantly improves the bundling and wear resistance of glass fiber yarns, reduces energy consumption, and meets the requirements of green development and weaving.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005108919690000071
    Figure BDA0005108919690000071
Patent Text Reader

Abstract

The invention discloses a preparation method and application of bio-based plastic starch slurry with medium-temperature water solubility, and belongs to the technical field of textile manufacturing. According to the invention, native starch is used as a raw material, starch is hydrolyzed by amylase to prepare branched limit dextrin, the branched limit dextrin is used as a starch slurry plasticizer, then amphoteric starch is prepared by two-step grafting in a low-temperature environment, and finally, the medium-temperature water-soluble amphoteric starch slurry is obtained by ethanol-alkali treatment. The temperature of the preparation, boiling, mixing and sizing process of the size does not exceed 70 DEG C, medium and low temperature is realized in the whole process, the energy consumption is greatly reduced, the sizing performance meets the weaving requirement, and the prepared bio-based plastic starch size with the medium-temperature water solubility has excellent sizing performance, and is suitable for large-scale production. And the sized glass fiber warp yarns have high bundling property, high wear resistance, excellent mechanical property and excellent flexibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a bio-based plastic starch slurry with medium-temperature water solubility, belonging to the technical field of textile manufacturing. Background Art

[0002] Usually, in the actual weaving process of glass fiber, due to external mechanical action, it is easy to produce broken ends, which in turn produces defects on the surface of the grey cloth, affecting the product quality. Therefore, in order to improve the physical and mechanical properties of glass fiber warp yarn and effectively reduce the yarn breakage rate, the glass fiber yarn needs to be sizing. Among them, the selection of sizing agent has a great influence on improving the quality of yarn. Excellent textile sizing agent needs to have the following characteristics: suitable viscosity, good liquid phase dispersion stability, excellent adhesion, excellent film-forming performance, and easy desizing and simple desizing wastewater treatment process. At present, the commonly used sizing agents for glass fiber yarn sizing are mainly divided into polyvinyl alcohol (PVA), acrylic acid and starch. PVA sizing agent was once called "ideal sizing agent" because of its excellent sizing performance, but its COD value is high, which puts a great burden on the environment; polyacrylic acid sizing agent is more environmentally friendly, but its composition is complex, the quality is uneven, and the price is expensive; starch has the advantages of being cheap, easy to obtain, and easy to degrade, but starch is difficult to dissolve in water, has poor film-forming properties, and the sizing film is brittle and hard.

[0003] Traditional starch slurry has many problems such as high-temperature sizing, viscosity fluctuation, serious pollution, and high energy consumption. In view of these problems, the existing technology has been improved, such as the preparation method of a medium-temperature starch slurry disclosed in Chinese patent CN112111018A. The starch slurry provided by the invention plasticizes the starch adhesive layer by means of steric hindrance through the introduction of amphiphilic functional groups. At the same time, the introduction of hydrophilic and hydrophobic functional groups can reduce the surface tension of the starch slurry, solving the problem of poor wetting and spreading of the starch junction layer and the fiber. Another example is the preparation method of a multi-branched cationic starch slurry for medium- and low-temperature warp sizing disclosed in Chinese patent CN116240724A. Through hydrolysis, cationic etherification and multi-branching, a multi-branched cationic starch slurry with a high degree of substitution is obtained. The invention process and the use process can be carried out under medium- and low-temperature environments, which can effectively reduce energy consumption, improve the utilization rate of etherifying agents, and significantly improve the working environment of workers, meeting the requirements of energy conservation, environmental protection and sustainable development. Another example is a sizing formula for medium-temperature sizing of pure cotton warp yarn disclosed in CN106319960B of China, which includes medium-temperature soluble starch and polyacrylic acid sizing. The invention blends the two components of medium-temperature soluble starch and polyacrylic acid sizing, and adjusts the sizing process so that the sized pure cotton yarn meets the weaving requirements. Due to the simple formula and easy sizing, the working environment of the workers in the sizing workshop is significantly improved and the enterprise cost is reduced; however, patent CN112111018A uses calcium oxide and phosphate substances in the starch preparation process. If they are not removed completely during the industrial production process, the ash residue will increase when the calcination method is used for desizing, resulting in defects and yellow spots on the glass fiber; patent CN106319960B uses polyacrylic acid slurry to blend with starch. Due to the complex composition of polyacrylic acid slurry, poor quality control, and high price, it cannot completely replace PVA slurry in glass fiber sizing, and has certain limitations; patent CN116240724A has multiple starch branches, which leads to weakened hydrophilicity and polarity of starch. When starch sizing, starch slurry cannot form a strong hydroxyl force with the silanol group on the surface of glass fiber, which weakens the affinity between starch slurry and glass fiber to a certain extent. Summary of the invention

[0004] [Technical issues]

[0005] At present, most of the existing medium and low temperature starch sizing agents are developed for traditional yarns, and the properties of the glass fiber itself and its sizing and desizing requirements are not considered. There are certain defects in the bundling of sizing yarns, the wear resistance of sizing yarns and the ash residue after desizing. For example, the glass fiber yarn has poor bundling, low wear resistance and excessive ash residue leaving yellow spots.

[0006] [Technical solution]

[0007] In order to solve the above problems, the present invention designs and develops a plastic starch slurry with medium-temperature water solubility. When the traditional starch slurry is used to size the glass fiber warp yarn, due to the brittleness of the starch film itself, it cannot effectively improve the wear resistance of the glass fiber warp yarn. The addition of the plasticizer prepared by enzymatic hydrolysis of starch improves the plasticity of the starch film; at the same time, due to the high viscosity of the slurry, it is difficult to penetrate between the fibers of the glass fiber warp yarn, and can only form adhesion with the glass fiber warp yarn on the surface. By introducing amphiphilic groups, the surface tension of the slurry is reduced, and the slurry is further penetrated into the interior of the yarn, thereby improving the bundling of the yarn; finally, the modified starch is treated by the ethanol alkali method, so that it can be dissolved and gelatinized at medium temperature, thereby reducing the energy consumption in the sizing process. The medium-temperature water-soluble plastic starch slurry prepared by the present invention not only conforms to the concept of green development but also meets the requirements of the subsequent weaving and reinforcement of glass fiber yarn.

[0008] In order to achieve the above purpose, the technical solutions provided are as follows:

[0009] A method for preparing a bio-based plastic starch slurry with medium-temperature water solubility, the method comprising the following steps:

[0010] (1) Preparation of starch dextrin: The gelatinized starch is kept warm in a water bath at 50-60°C and adjusted to pH 6 with an acetate buffer, α-amylase is added for reaction, the pH of the system is adjusted to 5.5 after the reaction, the temperature is lowered to 45-55°C, β-amylase is added for reaction, the enzyme is inactivated after the reaction, the starch is separated by ethanol sedimentation method and centrifuged, the precipitate is collected and freeze-dried to obtain starch dextrin A;

[0011] (2) Cross-linking modification: the original starch is dispersed in deionized water to prepare a starch emulsion, and then a cross-linking agent is added to the starch emulsion to react. After the reaction, the starch emulsion is neutralized to a pH of 7 to 8, and the starch emulsion is filtered and washed, and finally dried and ground into powder to obtain modified starch A;

[0012] (3) Cationic modification: The modified starch A obtained in step (2) is dispersed in deionized water to prepare a starch emulsion, the starch emulsion is placed in a four-necked flask under a nitrogen environment, and a cationic monomer and a catalyst are added to react. After the reaction is completed, the emulsion is filtered and washed, and then dried and ground into powder to obtain a modified starch B;

[0013] (4) Preparation of medium-temperature water-soluble starch: Disperse the modified starch B prepared in step (3) in an ethanol-water solution with a volume ratio of 1:1 in a water bath at 50-60° C. to prepare a starch emulsion, then add a sodium hydroxide solution prepared with an ethanol-water solution with a volume ratio of 1:1, keep warm and then centrifuge, wash the precipitate after centrifugation, and vacuum dry to obtain medium-temperature water-soluble starch C;

[0014] (5) Slurry preparation: The medium-temperature water-soluble starch C prepared in step (4) and the starch dextrin A prepared in step (1) are dispersed in deionized water to prepare starch milk, and the starch milk is placed in a pulp cooking barrel and gelatinized at 60 to 70° C. to obtain a bio-based plastic starch slurry with medium-temperature water solubility.

[0015] In one embodiment, the mass fraction of the gelatinized starch in step (1) is 40-45%.

[0016] In one embodiment, the time for adding α-amylase to react in step (1) is 24 to 36 hours.

[0017] In one embodiment, the time for adding β-amylase to react in step (1) is 24 to 48 hours.

[0018] In one embodiment, the native starch in step (2) includes one or more of corn starch, tapioca starch, potato starch, sweet potato starch, and wheat starch.

[0019] In one embodiment, the cross-linking agent in step (2) includes one or more of epichlorohydrin, glycerol diglycidyl ether, ethylene glycol diglycidyl ether, glycidyl methacrylate, 1,4-butanediol diglycidyl ether, ethoxy epichlorohydrin, and acrylamide.

[0020] In one embodiment, the mass fraction of starch in the reaction system of step (2) is 30-50%, the mass fraction of the cross-linking agent is 0.5-2%, and the reaction time is 4-6 hours.

[0021] In one embodiment, NaCl solution and NaOH solution are further added to the reaction system in step (2), wherein the mass fraction of the NaCl solution is 1%, the mass fraction of the NaOH solution is 15%, and the volume ratio of the NaCl solution to the NaOH solution is 2:1.

[0022] In one embodiment, the mass fraction of starch milk in the reaction system of step (3) is 30-60%.

[0023] In one embodiment, the cationic monomer in step (3) includes one or more of 3-chloro-2-hydroxypropyltrimethylammonium chloride, methacryloyloxyethyltrimethylammonium chloride, acryloylchloropropyltrimethylammonium chloride, methacryloyloxypropyldimethylethylammonium chloride, acryloyloxypropyltrimethylammonium chloride, dimethyldiallylammonium chloride, methacryloyloxyethyldimethylphenethylammonium chloride, acryloyloxyethyltrimethylmethylammonium chloride, and methacryloyloxyethyldimethylalkylammonium chloride.

[0024] In one embodiment, the catalyst in step (3) is one or more of cerium ammonium nitrate, ammonium persulfate, potassium persulfate, sodium persulfate, hydrogen peroxide, benzoyl peroxide, tert-butyl peroxide, diisopropyl peroxide, dibenzoyl peroxide, azobisisobutyronitrile (AIBN), sodium hydroxide, potassium hydroxide, ferric chloride, zinc chloride, and potassium permanganate.

[0025] In one embodiment, the mass fraction of the cationic monomer in step (3) is 1-2%.

[0026] In one embodiment, the mass fraction of the catalyst in step (3) is 0.1-0.5%.

[0027] In one embodiment, the reaction time of step (3) is 4 to 6 hours.

[0028] In one embodiment, the mass fraction of the starch milk in step (4) is 30-60%.

[0029] In one embodiment, the mass fraction of the sodium hydroxide solution in step (4) is 1 to 5%.

[0030] In one embodiment, the insulation time in step (4) is 0.5 to 2 hours.

[0031] In one embodiment, the mass ratio of the medium-temperature water-soluble starch C and starch dextrin A in step (5) is 8 to 12:1.

[0032] In one embodiment, the mass fraction of the starch milk in step (5) is 2-6%.

[0033] The present invention also provides a bio-based plastic starch slurry with medium-temperature water solubility for sizing glass fiber warp yarns prepared by the above method.

[0034] The present invention also provides the use of the bio-based plastic starch sizing material with medium-temperature water solubility for sizing glass fiber warp yarns in sizing glass fiber yarns.

[0035] Beneficial effects:

[0036] The present invention prepares a green slurry that can be dissolved at medium temperature, and the slurry can significantly improve the bundling and wear resistance of glass fiber. Corn starch is used as raw material, starch is hydrolyzed by amylase to prepare branched limit dextrin, and it is used as a starch slurry plasticizer, and then amphoteric starch is prepared by grafting in a two-step method under a low temperature environment, and finally an ethanol-alkali method is used to obtain a medium-temperature water-soluble amphoteric starch slurry. The temperature of the slurry preparation, slurry cooking and sizing process does not exceed 70°C, and medium and low temperatures are achieved in the entire process, which greatly reduces energy consumption and the sizing performance meets the weaving requirements; compared with the existing technology, it has the following advantages:

[0037] (1) The bio-based plastic starch slurry with medium-temperature water solubility prepared by the present invention has excellent sizing performance; the glass fiber warp yarn after sizing has high bundling, high wear resistance, excellent mechanical properties and excellent softness;

[0038] (2) The present invention grafts modified starch slurry through a two-step method, which can effectively improve the permeability of starch slurry to glass fiber and improve the bundling of glass fiber warp yarn after sizing. At the same time, starch dextrin is used as a plasticizer to improve the softness and wear resistance of glass fiber warp yarn after sizing while ensuring good compatibility with starch. DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. The following specific implementation methods further describe the present invention.

[0040] Example 1

[0041] A method for preparing a bio-based plastic starch slurry with medium-temperature water solubility comprises the following steps:

[0042] (1) Preparation of starch dextrin: A 40% gelatinized starch milk was kept warm in a 60°C water bath and adjusted to pH 6 with an acetate buffer. α-amylase was added. After reacting for 24 hours, the pH of the system was adjusted to 5.5. The temperature was lowered to 55°C, and β-amylase was added to react for 48 hours. After the reaction was completed, the enzyme activity was inactivated by boiling, separated by ethanol sedimentation, and centrifuged. The precipitate was collected and freeze-dried, and the obtained starch dextrin A was stored for later use.

[0043] (2) Cross-linking modification: corn starch was dispersed in deionized water to prepare starch milk, 10 ml of 1% NaCl solution was added, and then 5 ml of 15% NaOH solution was added to the starch milk. After stirring for 0.5 h, a certain amount of epichlorohydrin was added dropwise to the starch milk to react. In the reaction system, the mass fraction of starch was 40% and the mass fraction of epichlorohydrin was 1%. The reaction was completed after 4 h. The starch milk was neutralized with 0.1 mol / L acetate buffer to a pH of 7, and the starch milk was filtered and washed. Finally, it was dried and ground into powder to obtain modified starch A.

[0044] (3) Cationic modification: the modified starch A prepared in step (2) is dispersed in deionized water to prepare a starch emulsion with a certain content, the starch emulsion is placed in a four-necked flask under a nitrogen environment, the water bath temperature is adjusted to 50° C., and a cationic monomer methacryloyloxyethyltrimethylammonium chloride and a catalyst ammonium cerium nitrate are added to react, wherein the mass fraction of starch in the reaction system is 40%, the mass fraction of methacryloyloxyethyltrimethylammonium chloride is 1%, and the mass fraction of ammonium cerium nitrate is 0.2%. After 4 hours, the reaction is completed, and the mixture is filtered and washed, and then dried and ground into powder to obtain modified starch B;

[0045] (4) Preparation of medium-temperature water-soluble starch: Under a 60° C. water bath condition, the modified starch B prepared in step (3) is dispersed in an ethanol-water solution with a volume ratio of 1:1 to prepare a starch milk with a mass fraction of 40%, and then 10 ml of a 5% sodium hydroxide solution prepared with an ethanol-water solution with a volume ratio of 1:1 is added. After keeping the temperature for 0.5 h, the precipitate after centrifugation is washed and vacuum dried to obtain medium-temperature water-soluble starch C;

[0046] (5) Slurry preparation: The medium-temperature water-soluble starch C prepared in step (4) and the starch dextrin A prepared in step (1) are dispersed in deionized water at a mass ratio of 10:1 to prepare a starch emulsion with a mass fraction of 6%. The starch emulsion is placed in a pulping barrel and gelatinized at 70° C. for 1 hour to obtain a medium-temperature water-soluble plastic slurry for sizing glass fiber warp yarns.

[0047] Example 2

[0048] A method for preparing a bio-based plastic starch slurry with medium-temperature water solubility, referring to Example 1, except that: step (3) cationic modification: the modified starch A prepared in step (2) is dispersed in deionized water to form a starch emulsion with a certain content, the starch emulsion is placed in a four-necked flask under a nitrogen environment, the water bath temperature is adjusted to 50°C, and a cationic monomer 3-chloro-2-hydroxypropyltrimethylammonium chloride and a catalyst sodium hydroxide are added to react, wherein, in the reaction system, the mass fraction of starch is 40%, the mass fraction of 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1%, and a 2% NaOH solution is used to adjust the system solution pH to 11 and act as a catalyst. After the reaction is completed for 4 hours, suction filtration and washing are performed, and the mixture is dried and ground into powder to obtain modified starch B; other parameters and conditions are the same as those in Example 1.

[0049] Example 3

[0050] A method for preparing a bio-based plastic starch slurry with medium-temperature water solubility, referring to Example 1, except that: Step (2) cross-linking modification: corn starch is dispersed in deionized water to prepare starch milk, 10 ml of a 1% NaCl solution is added, and 5 ml of a 15% NaOH solution is added to the starch milk. After stirring for 0.5 h, a certain amount of acrylonitrile is added dropwise to the starch milk to react, wherein the mass fraction of starch in the reaction system is 40%, and the mass fraction of acrylonitrile is 1%. The reaction is completed after 4 h, and the starch milk is neutralized with 0.1 mol / L acetate buffer to a pH of 7, and the starch milk is filtered and washed, and finally dried and ground into powder to obtain modified starch A. Other parameters and conditions are the same as those in Example 1.

[0051] Example 4

[0052] A method for preparing a bio-based plastic starch slurry with medium-temperature water solubility, referring to Example 1, except that: Step (2) cross-linking modification: corn starch is dispersed in deionized water to prepare starch milk, 10 ml of a 1% NaCl solution is added, and then 5 ml of a 15% NaOH solution is added to the starch milk. After stirring for 0.5 h, a certain amount of diketene is added dropwise to the starch milk to react, wherein the mass fraction of starch in the reaction system is 40%, and the mass fraction of diketene is 1%. The reaction is completed after 2 h, and the starch milk is neutralized with 0.1 mol / L acetate buffer to a pH of 7, and the starch milk is filtered and washed, and finally dried and ground into powder to obtain modified starch A. Other parameters and conditions are the same as those in Example 1.

[0053] Example 5

[0054] A method for preparing a bio-based plastic starch slurry with medium-temperature water solubility, with reference to Example 1, except that: step (3) cationic modification: the modified starch A prepared in step (2) is dispersed in deionized water to prepare a starch emulsion with a certain content, the starch emulsion is placed in a four-necked flask under a nitrogen environment, the water bath temperature is adjusted to 50° C., a cationic monomer 2-acryloyloxytrimethylammonium chloride and a catalyst ammonium persulfate are added to react, wherein, in the reaction system, the mass fraction of starch is 40%, the mass fraction of 2-acryloyloxytrimethylammonium chloride is 1%, and the mass fraction of ammonium persulfate is 0.1%. After 4 hours, the reaction is completed, and the starch is filtered and washed, and then dried and ground into powder to obtain modified starch B. Other parameters and conditions are the same as those in Example 1.

[0055] Comparative Example 1

[0056] A method for preparing a medium-temperature water-soluble plastic starch slurry is described with reference to Example 1, except that trimethylolpropane acrylate is used as a crosslinking agent in step (2), and other parameters and conditions are the same as those in Example 1.

[0057] Comparative Example 2

[0058] A method for preparing a medium-temperature water-soluble plastic starch slurry is described with reference to Example 1, except that acryloyloxypropyltrimethylammonium chloride is used as a cationic monomer in step (3), and other parameters and conditions are the same as those in Example 1.

[0059] Comparative Example 3

[0060] A method for preparing a medium-temperature water-soluble plastic starch slurry is described with reference to Example 1, except that starch dextrin is not added in step (5), and other parameters and conditions are the same as those in Example 1.

[0061] Comparative Example 4

[0062] A method for preparing a medium-temperature water-soluble plastic starch slurry is described with reference to Example 1, except that step (4) is not performed, and other parameters and conditions are the same as those in Example 1.

[0063] Comparative Example 5

[0064] Referring to Example 1 disclosed in CN112111018A, 3-chloro-2-hydroxypropyltrimethylammonium chloride was used as a cationic monomer and itaconic anhydride was used as a cross-linking agent for amphiphilic modification, and finally sodium polyphosphate was used for treatment to obtain a medium-temperature starch slurry.

[0065] Example 6

[0066] The plastic starch slurry with medium-temperature water solubility prepared in Examples 1 to 5 and Comparative Examples 1 to 5 is used in sizing glass fiber yarn. The glass fiber yarn used is 24-count, 1-ply alkali-free waxed glass fiber yarn provided by Yushun Textile Co., Ltd. The sizing process includes the following steps:

[0067] A GA392 electronic single yarn sizing machine was used for the sizing test. The sizing tank temperature was set to 70°C. Medium-temperature water-soluble plastic starch slurry was poured into the sizing tank. The glass fiber yarn was wound on the sizing machine for sizing. The sizing speed was 20m / min, the sizing tension was 0.5N, and the yarn tube was taken out after sizing to obtain the product.

[0068] Results Analysis

[0069] According to the method of Example 6, the medium-temperature water-soluble plastic starch slurry prepared in each embodiment and comparative example was used to size the glass fiber yarn, and the wear resistance of the product was tested by the wear tester test method with reference to the standard FZ / T01058-1999 "Yarn Wear Test Method Reciprocating Grinding Roller Method", and the number of friction fractures was used as the wear resistance index; the performance test was performed with reference to GB / T7690.3-2013 Determination of the breaking strength and breaking elongation of textile glass fiber yarn, and the results are summarized in Table 1:

[0070] Table 1. Breaking strength and breaking elongation of glass fiber yarn

[0071]

[0072] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.

Claims

1. A method for preparing a bio-based plastic starch slurry with medium-temperature water solubility, characterized in that: The method comprises the following steps: (1) Preparation of starch dextrin: The gelatinized starch is kept warm in a water bath at 50-60°C and adjusted to pH 6 with an acetate buffer, α-amylase is added for reaction, the pH of the system is adjusted to 5.5 after the reaction, the temperature is lowered to 45-55°C, β-amylase is added for reaction, the enzyme is inactivated after the reaction, the starch is separated by ethanol sedimentation method and centrifuged, the precipitate is collected and freeze-dried to obtain starch dextrin A; (2) Cross-linking modification: the original starch is dispersed in deionized water to prepare a starch emulsion, and then a cross-linking agent is added to the starch emulsion to react. After the reaction, the starch emulsion is neutralized to a pH of 7 to 8, and the starch emulsion is filtered and washed, and finally dried and ground into powder to obtain modified starch A; (3) Cationic modification: The modified starch A obtained in step (2) is dispersed in deionized water to prepare a starch emulsion, the starch emulsion is placed in a four-necked flask under a nitrogen environment, and a cationic monomer and a catalyst are added to react. After the reaction is completed, the emulsion is filtered and washed, and then dried and ground into powder to obtain a modified starch B; (4) Preparation of medium-temperature water-soluble starch: Disperse the modified starch B prepared in step (3) in an ethanol-water solution with a volume ratio of 1:1 in a water bath at 50-60° C. to prepare a starch emulsion, then add a sodium hydroxide solution prepared with an ethanol-water solution with a volume ratio of 1:1, keep warm and then centrifuge, wash the precipitate after centrifugation, and vacuum dry to obtain medium-temperature water-soluble starch C; (5) Slurry preparation: The medium-temperature water-soluble starch C prepared in step (4) and the starch dextrin A prepared in step (1) are dispersed in deionized water to prepare starch milk, and the starch milk is placed in a pulping barrel and gelatinized at 60 to 70° C. to obtain a bio-based plastic starch slurry with medium-temperature water solubility.

2. The preparation method according to claim 1, characterized in that: The mass fraction of the gelatinized starch in step (1) is 40-45%.

3. The preparation method according to claim 1, characterized in that: The native starch in step (2) includes one or more of corn starch, tapioca starch, potato starch, sweet potato starch, and wheat starch.

4. The preparation method according to claim 1, characterized in that: The cross-linking agent in step (2) includes one or more of epichlorohydrin, glycerol diglycidyl ether, ethylene glycol diglycidyl ether, glycidyl methacrylate, 1,4-butanediol diglycidyl ether, ethoxy epichlorohydrin, and acrylamide.

5. The preparation method according to claim 1, characterized in that: In step (2), the mass fraction of starch in the reaction system is 30-50%, the mass fraction of the cross-linking agent is 0.5-2%, and the reaction time is 4-6 hours.

6. The preparation method according to claim 1, characterized in that: The cationic monomer in step (3) includes one or more of 3-chloro-2-hydroxypropyltrimethylammonium chloride, methacryloyloxyethyltrimethylammonium chloride, acryloylchloropropyltrimethylammonium chloride, methacryloyloxypropyldimethylethylammonium chloride, acryloyloxypropyltrimethylammonium chloride, dimethyldiallylammonium chloride, methacryloyloxyethyldimethylphenethylammonium chloride, acryloyloxyethyltrimethylmethylammonium chloride, and methacryloyloxyethyldimethylalkylammonium chloride.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the medium-temperature water-soluble starch C and starch dextrin A in step (5) is 8 to 12:

1.

8. The preparation method according to claim 1, characterized in that: The mass fraction of the starch milk in step (5) is 2-6%.

9. A bio-based plastic starch slurry with medium-temperature water solubility for sizing glass fiber warp yarns obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the bio-based plastic starch sizing material with medium-temperature water solubility for sizing glass fiber warp yarns as claimed in claim 9 in sizing glass fiber yarns.

Citation Information

Patent Citations

  • A sizing agent and sizing method for sizing pure cotton warp yarns

    CN106319960B

  • Preparation method of medium-temperature starch slurry

    CN112111018A

  • Granular cold water soluble porous starch

    CN101824165A

  • Preparation method of high viscosity cationic starch

    CN102382197A

  • Preparation method of cationic starch with high substituted degree

    CN104497152A